Double duct sign - Brij Sharma; Sujeet Raina; Neetu Sharma; Rajesh Sharma (Wolters Kluwer Medknow Publications, 2016)
Double duct sign is an anatomical sign of combined dilatation of common bile duct and pancreatic duct. It is observed on imaging during endoscopic retrograde cholangio-pancreatography, magnetic resonance cholangio-pancreatography, computed tomography and ultrasound. The sign in a jaundiced patient is highly diagnostic of pancreatic carcinoma.